2015
DOI: 10.2306/scienceasia1513-1874.2015.41.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Morinda citrifolia leaf extract on macrophage RAW 264.7 cells

Abstract: Leaves of Morinda citrifolia (Rubiaceae) have been used in folk medicine to treat pain and inflammation. In this study, the anti-inflammatory activity of M. citrifolia leaf extracts was investigated. The extract was prepared by freeze-drying juice squeezed from M. citrifolia leaves. HPLC analysis of the crude extract revealed rutin to be a major compound together with small amounts of quercetin and kaempferol. The effect of this extract on TNF-α, IL-1β, and NO secretion by lipopolysaccharide-induced macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…Plants are the excellent source of antioxidant molecules that effectively inhibit the inflammatory process by affecting different molecular targets, and numerous natural products have been assessed in various in vivo and in vitro models for discovering new anti‐inflammatory agents. LPS, a component from the cell walls of Gram ‐negative bacteria, is used to involve the production of pro‐inflammatory cytokines from macrophages . Inhibition of NO production in LPS‐stimulated RAW 264.7 cells, was tested for the MeOH, 70% MeOH, and water extracts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants are the excellent source of antioxidant molecules that effectively inhibit the inflammatory process by affecting different molecular targets, and numerous natural products have been assessed in various in vivo and in vitro models for discovering new anti‐inflammatory agents. LPS, a component from the cell walls of Gram ‐negative bacteria, is used to involve the production of pro‐inflammatory cytokines from macrophages . Inhibition of NO production in LPS‐stimulated RAW 264.7 cells, was tested for the MeOH, 70% MeOH, and water extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages are responsible for production of pro‐inflammatory cytokines and inflammatory molecules that are necessary for the inflammatory process. In case of a stimulus, various cytokines, such as tumor necrosis factor‐ α (TNF‐ α ), interleukin‐1 β (IL‐1 β ), interleukin‐6 (IL‐6), and interleukin‐10 (IL‐10), and inflammatory mediators such as nitric oxide (NO) and prostaglandin E2 (PGE2) are produced from activated macrophages . Previous studies showed that antioxidants may provide a useful approach in the cellular injury and dysfunction observed in some inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with MC leaf extract maintained the normal histology and ultrastructure of the aorta comparable to that of the Sham group. The mechanism of action of MC leaf is due to the presence of flavanoids such as rutin, kaempferol, and quercetin which showed inhibitory effects against proinflammatory cytokines (TNF- α , IL-1B, and NO) [19]. -carotene in the MC leaf also acts as a potent antioxidative agent [14].…”
Section: Discussionmentioning
confidence: 99%
“…Phytoactive substances isolated from the leaf include β -carotene [14], kaempferol [15], quercetin, rutin [16], and ursolic acid [17]. These substances were shown to possess anti-inflammatory [18, 19], antidyslipidemic [20], and antioxidant activities [21]. This study aimed to validate the traditional uses of MC leaf extract (MCLE) as a medicinal food in Traditional Malay Medicine [22] by investigating the protective effects of the leaf extract on the aortic structure and cardiovascular function in ovariectomized rats fed with TPO diet for a period of 12 weeks, with emphasis on the aortic tissue histological and ultrastructural findings.…”
Section: Introductionmentioning
confidence: 99%